Status epilepticus - Lowenstein, Daniel (Henry Stewart Talks, 2011)
Generalized status epilepticus, Evolution of the definition of status epilepticus, Epidemiological studies of status epilepticus, Basic mechanisms of status epilepticus, Treatment approaches for status epilepticus in the hospital and out-of-hospital settings